Penerapan Model Pembelajaran Problem Base Learning (PBL) pada Pembelajaran IPA - Kholida Ismatulloh; Ropikoh Ropikoh (Kappa Journal, 2021)
The study, entitled "Application of the Problem Base Learning Model in Science Lessons at SMPN 3 Selong" aims to determine the influence of students in  understanding  the  concept  of  learning  science  in  the  classroom.  The research subjects were students of class VIII at SMPN 3 Selong, namely class VIII A and class VIII B, with the data retrieval process using a written test of 5 items of description. The average value obtained in the control class is 65.48 while the experimental class is 85.48 with a difference of 20 points. For the hypothesis value   = 2.042 while   = 1.079 from the results of the calculation of the hypothesis test results of learning science students obtained  >  =, then the hypothesis alternative (Ha) is accepted. So it can be concluded that there is an influence in the application of the Problem Base Learning model in science learning at SMP 3 Selong